Gender Transformative Approach (GTA) and SASA-Together - Nemera Woyessa, Martha; Najjar, Dina; Tsige, Meseret (2024)
ICARDA has scheduled training on gender transformative approach to implement selected GTA approach in the CGIAR Initiative Projects: Sustainable Animal Productivity for Likelihoods, Nutrition and Gender Inclusion (SAPLING) and Sustainable Intensification of Mixed Farming System (SI-MFS). The training is intended to improve participants' understanding of gender, gender transformative approach and social norms that restrict the cooperatives established by the project gender equitable benefit from the project. A six-day gender training was provided for participants drawn from Areka Agricultural Research centers, Women, children, and Social Affairs, Midea Agency and community data collectors from Serera and Lemi kebele of Doyogena District, South Ethiopia Region.